Policy Text AI Mining Study —— A Comparative Analysis Based on U.S., U.K., and Chinese Policies - Wang, Zixian (Transactions on Economics, Business and Management Research, 2024)
Artificial Intelligence (AI) has become a key strategic area to enhance national competitiveness globally. We adopts a textual analysis methodology, based on the three-dimensional framework of policy tools and the LDA thematic model, to conduct a systematic analysis and comparative study of the AI policy texts of the United States, the United Kingdom, and China. The study aims to reveal the policy stance, strategic planning, and challenges and opportunities faced by the three countries in the field of AI. Through the analysis, the study identifies the major themes in the policy texts of each country and maps them to the three dimensions of supply, demand, and environment of policy tools. The study finds that the US AI policy focuses on international cooperation, fair civil rights, and innovation ecology; the UK emphasizes ethical governance and legal regulation; and China highlights innovation-driven and smart economy development. In addition, all three countries emphasize building a stable, predictable and innovation-supportive policy environment. The study puts forward a series of comprehensive recommendations, including strengthening international cooperation, balancing innovation and regulation, optimizing a supportive innovation ecosystem, improving the legal system, focusing on talent cultivation, and building an AI innovation alliance. These recommendations aim to promote the healthy development of global AI technologies and maximize their positive contributions to the economy and society.